Sex and Racial/Ethnic Differences in Home Hemodialysis Mortality. Issue 2 (18th February 2023) - Shah, Silvi; Gupta, Nupur; Christianson, Annette L.; Meganathan, Karthikeyan; Leonard, Anthony C.; Thakar, Charuhas V.
Abstract : Abstract : Key Points: Women on home hemodialysis have higher 1-year mortality than men, and women and men have comparable survival on long-term follow-up. Compared with White patients on home hemodialysis, there was no difference in all-cause mortality for Black patients, Hispanics, or Native Americans. Among patients undergoing home hemodialysis, Asians had a lower risk of all-cause mortality than White patients. Background: Women and minorities constitute substantial portions of the prevalent population of patients with kidney failure. Little is known about sex and racial/ethnic differences in mortality among patients with kidney failure on home hemodialysis in the United States. Methods: Using the United States Renal Data System, we retrospectively evaluated a cohort of 42, 849 patients who started home hemodialysis between January 1, 2005, and December 31, 2015. We examined the association of sex and race/ethnicity with the outcome of all-cause mortality using adjusted Cox proportional hazard models and logistic regression models. Results: In the study cohort, 40.4% were women, and 57.4% were White. Women on home hemodialysis had higher unadjusted death rates (26.9 versus 22.4 per 100 person-years) compared with men. There was no difference in adjusted all-cause mortality between men and women, but women had an 8% higher adjusted risk of all-cause mortality at 1 year after initiating home hemodialysis (odds ratio 1.08, 95% confidence interval [CI], 1.01 to 1.15). Regarding race/ethnicity, Hispanic, White, and Black patients had higher unadjusted death rates compared with Asians and Native Americans (25.1 versus 24.8 versus 23.2 versus 17.4 versus 16.6 per 100 person-years). There was no difference in adjusted all-cause mortality in Black, Hispanic, and Native Americans compared with White patients, while Asians had a lower risk of all-cause mortality than did White patients (hazard ratio, 0.81; 95% CI, 0.72 to 0.92). There was no difference in adjusted 1-year mortality for Asian, Black, Hispanic, and Native American patients compared with White patients. Conclusions: Among patients undergoing home hemodialysis, women have higher 1-year mortality than men, and women and men have comparable survival on long-term follow-up after adjusting for other covariates. Compared with White patients, there was no difference in adjusted survival on long-term follow-up for Black patients, Hispanics, or Native Americans, while Asians had better survival. Our results suggest the need for population-wide strategies to overcome differences in home hemodialysis care.